Urgensi Pendidikan Keluarga dalam Membangun Moral Bangsa di Era Disrupsi - Rahayu, Rofita; Mukhtar, Tatang (QUALITY, 2024)
The Urgency of Family Education in Building National Morals in the Era of Disruption. This study aims to explore the scope of family education which is the main thing in the moral formation of the nation's children in the era of disruption. In this technological age, the nature of family education has faded, so that family education that should be used as education first and foremost has shifted to an education that is not too important. Moral education for children can change the child's behaviour, so that when the child grows up, he can be more responsible and respect fellow humans and able to face the world. Therefore, researchers made a study that will discuss the urgency of family education in building the nation's morals in an era of disruption. This research uses a research method, namely qualitative research with literature studies (library research).  The results of the study found that education in the family became the basis of an education and for further education. The role of parents is a factor that cannot be separated from family education. Parents have a role in their family education, namely nurturing children, guiding, forming good morals, and setting a good example for their children.Studi ini bertujuan untuk mendalami ruang lingkup pendidikan keluarga yang merupakan hal utama dalam pembentukan moral anak bangsa di era disrupsi. Pada zaman teknologi ini hakikat pendidikan keluarga telah memudar, sehingga pendidikan keluarga yang semestinya dijadikan pendidikan pertama dan utama telah bergeser menjadi sebuah pendidikan yang tidak terlalu penting. Pendidikan moral bagi anak dapat mengubah perilaku anak tersebut, sehingga ketika anak sudah dewasa bisa lebih bertanggung jawab dan menghargai sesama manusia dan mampu menghadapi dunia. Sebab itu, peneliti membuat sebuah penelitian yang akan membahas urgensi pendidikan keluarga dalam membangun moral bangsa di era disrupsi. Penelitian ini menggunakan metode penelitian yaitu penelitian kualitatif dengan studi literatur (library research). Hasil penelitian menemukan simpulan bahwa pendidikan dalam keluarga menjadi dasar dari sebuah pendidikan dan untuk pendidikan selanjutnya. Peran orang tua menjadi faktor yang tidak terlepas dari pendidikan keluarga. Orang tua memiliki peran dalam pendidikan keluarganya yaitu mengasuh anak, membimbing, membentuk moral yang baik, serta memberi teladan baik bagi anaknya.